PELATIHAN PENULISAN ARTIKEL POPULER BERBASIS KEARIFAN LOKAL BAGI MASYARAKAT KARANGANYAR JAWA TENGAH - Isnaniah, Siti; Hasanah, Dian Uswatun; Rahmawati, Endang (Dimasatra, 2021)
The people of Karanganyar, Central Java, have a high enthusiasm for writing literacy culture, one of which is the writing community of Forum Lingkar Pena (FLP), which always carries civilization by writing to provide enlightenment to the community. Their enthusiasm still needs to be honed because their writings are not fully in accordance with the guidelines for writing popular articles. Therefore, the TBI FAB IAIN Surakarta Study Program organizes Community Service (PkM) activities in the form of training in writing popular articles about local wisdom for the community. This activity aims to increase the role and contribution of FLP in improving the literacy culture for the Karanganyar community. The method of this activity includes preparatory meetings, meeting to determine participants, sending application letters and the place of implementation, sending participant invitation letters, technical preparation and accommodation, preparation of activity reports, submission of activity documents to FAB. The result of this activity was that the participants were very enthusiastic about participating in the training activities. The enthusiasm of the participants can be seen from the popular articles that have been made. In general, they are able to apply popular article writing, but there are some things that are not paid attention to in terms of leads, topics, titles, subtitles, vocabulary selection, outline, and content.